Proton gradients from light-harvesting E. coli control DNA assemblies for synthetic cells - Kevin Jahnke (Nature Portfolio, 2021)
Controlled actuation is an important aspect of synthetic cellular systems. Here, the authors combine pH responsive DNA origami structures with light triggered proton pump engineered E. coli to trigger a change in pH and control the deformation of giant unilamellar vesicles by simple illumination.